Metrics in automotive software development: A systematic literature review. Issue 2 (12th August 2020) - Vogel, Martin; Knapik, Peter; Cohrs, Moritz; Szyperrek, Bernd; Pueschel, Winfried; Etzel, Haiko; Fiebig, Daniel; Rausch, Andreas; Kuhrmann, Marco
Abstract: Software is an integrated part of new features within the automotive sector, car manufacturers, the Hersteller Initiative Software (HIS) consortium defined metrics to determine software quality. Yet, problems with assigning metrics to quality attributes often occur in practice. The specified boundary values lead to discussions between contractors and clients as different standards and metric sets are used. This paper studies metrics used in the automotive sector and the quality attributes they address. The HIS, ISO/IEC 25010:2011, and ISO/IEC 26262:2018 are utilized to draw a big picture illustrating (i) which metrics and boundary values are reported in literature, (ii) how the metrics match the standards, (iii) which quality attributes are addressed, and (iv) how the metrics are supported by tools. Our findings from analyzing 38 papers include a catalog of 112 metrics of which 17 define boundary values and 48 are supported by tools. Most of the metrics are concerned with source code, are generic, and not specifically designed for automotive software development. We conclude that many metrics exist, but a clear definition of the metrics' context, notably regarding the construction of flexible and efficient measurement suites, is missing. Abstract : We present a catalog of 112 metrics obtained from a systematic literature review. The metrics were mapped to the 15 HIS‐metrics, which are used in the field of Automotive software engineering, the ISO‐standards 25011:2011, 25023:2016 and 26262:2018, and to 20 selected tools to study the tool‐support for metrics. Our findings show that most of the found metrics are generic, that boundary values are scarcely defined, and that a missing clear understanding of the metrics' context limits the definition of flexible and efficient measurement suites.